The Synonymy Of Tolea-Pabitara Utterances In Marriage Tradition Of Tolakinese - Iin Wahyudi; Mclean HY; Nuryadin Nuryadin (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This research aimed to know the pattern and the form of Synonymy of Tolaki language uttered by Tolea-Pabitara in the marriage tradition. This research used an analysis qualitative descriptive design by applying some techniques of collecting data as follows: (1) Interview, (2) Recording. To get the data about The Synonymy In Tolea-Pabitara Utterances In Marriage Tradition Of Tolakinese, the researcher use three methods, they are (1) Library method, (2) Field method and (3) Documentation. The researcher analyzed them through the following steps: (1) Transcription of the data, (2) Description the pattern of synonymy in Tolaki language through utterences of Tolea–Pabitara in marriage tradition of Tolakinese and followed by sentences of Tolea-Pabitara utterances, and (3) Description about the form of synonymy in utterances of Tolea–Pabitara in marriage tradition of Tolaki language. In this research, the researcher found two (2) pattern of scale namely (1) Double Scale and(2) Three Scale in Tolea-Pabitara utterances. There are 88 synonymy in Double Scale and there are 10 synonymy in Three Scale. Meanwhile, there are five (5) Form in the utterances of Tolea-Pabitara, theyare Noun, Verb, Adjective, Adverb and Interjection.